2019
DOI: 10.1503/jpn.180243
|View full text |Cite
|
Sign up to set email alerts
|

Time heals all wounds? A 2-year longitudinal diffusion tensor imaging study in major depressive disorder

Abstract: Background: Cross-sectional studies have repeatedly shown impaired white matter integrity in patients with major depressive disorder. Longitudinal analyses are missing from the current research and are crucial to elucidating the impact of disease trajectories on white matter impairment in major depressive disorder. Methods: Fifty-nine patients with major depressive disorder receiving inpatient treatment, as well as 49 healthy controls, took part in a prospective study. Participants were scanned twice (baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Repple et al examined the alterations of fractional anisotropy (FA), mean diffusivity, radial diffusivity and axial diffusivity in MDD patients throughout a 2-year treatment course. Patients with current depression showed higher mean diffusivity in the prefrontal lobe, which was dissipated at the remission phase (18). Based on these findings, white matter microstructural abnormalities seemed to be statedependent alterations fluctuating with depression symptoms in the pathogenesis of MDD.…”
Section: Introductionmentioning
confidence: 79%
“…Repple et al examined the alterations of fractional anisotropy (FA), mean diffusivity, radial diffusivity and axial diffusivity in MDD patients throughout a 2-year treatment course. Patients with current depression showed higher mean diffusivity in the prefrontal lobe, which was dissipated at the remission phase (18). Based on these findings, white matter microstructural abnormalities seemed to be statedependent alterations fluctuating with depression symptoms in the pathogenesis of MDD.…”
Section: Introductionmentioning
confidence: 79%
“…We used the nonparametric permutation testing implemented in FSL's “randomize” with 5,000 permutations, to test for statistical significance. Threshold‐free cluster enhancement (TFCE; Smith & Nichols, 2009), a previously employed method (Repple et al, 2019; Repple, Karliczek, et al, 2019) to correct for multiple comparisons, allows estimation of cluster sizes corrected for the family‐wise error (FWE; p < .05, 5,000 permutations). MNI coordinates and cluster size at peak voxel were derived with FSL Cluster and the corresponding WM tract retrieved from the ICBM‐DTI‐81 white‐matter atlas (Pekar et al, 2007; Repple et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…To completely disentangle the effects of acute symptomatology and course of illness, future longitudinal studies are necessary. In small groups of MDD patients, longitudinal studies found either associations between fiber integrity changes over the follow-up period and depressive symptom changes (Bracht, Jones, Müller, Wiest, & Walther, 2015; Doolin et al, 2019) or no association with course of illness or symptom severity, respectively (Repple et al, 2019). The largest longitudinal study to date ( N = 18 959) underscores the importance of the longitudinal illness burden (Shen et al, 2019): Although decreased white matter microstructure was linked to depressive symptoms, the strongest association was found for the longitudinal progression of depressive symptoms in fronto-temporal association fibers.…”
Section: Discussionmentioning
confidence: 99%